2018
DOI: 10.1002/2017gl076630
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 Observations Reveal Strong Correlation Between Regional Net Biospheric Carbon Uptake and Solar‐Induced Chlorophyll Fluorescence

Abstract: Recent studies have shown the promise of remotely sensed solar‐induced chlorophyll fluorescence (SIF) in informing terrestrial carbon exchange, but analyses have been limited to either plot level (~1 km2) or hemispheric/global (~108 km2) scales due to the lack of a direct measure of carbon exchange at intermediate scales. Here we use a network of atmospheric CO2 observations over North America to explore the value of SIF for informing net ecosystem exchange (NEE) at regional scales. We find that SIF explains s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 89 publications
7
47
0
Order By: Relevance
“…We see similar developments in the estimation of CO 2 fluxes (e.g. Tans et al, 1990vs Chevallier et al, 2010 and ocean productivity (Balkanski et al, 1999cf. Brasseur et al, 2009.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…We see similar developments in the estimation of CO 2 fluxes (e.g. Tans et al, 1990vs Chevallier et al, 2010 and ocean productivity (Balkanski et al, 1999cf. Brasseur et al, 2009.…”
Section: Introductionsupporting
confidence: 80%
“…They are still widely used (e.g. Fang et al, 2014;Fang and Michalak, 2015;Henne et al, 2016;Saeki and Patra, 2017;Chen et al, 2017;Shiga et al, 2018;Wang et al, 2018). Originally Jacobians were generated with multiple forward runs, each run corresponding to a desired source component.…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical analytical methods (Section 6.4) were the first workhorse for flux inversions of inert tracers like CO 2 where the problem is linear. They are still widely used (e.g., Fang et al, 2014;Fang and Michalak, 2015;Henne et al, 2016;Saeki and Patra, 2017;Chen et al, 2017;Shiga et al, 2018;Wang et al, 2018). Originally Jacobians were generated with multiple forward runs, each run corresponding to a desired source component.…”
Section: Historical Overviewmentioning
confidence: 99%
“…Previous studies have demonstrated the potential for detecting and deriving urban CO 2 emission signals from satellite CO 2 observations, in the form of XCO 2 enhancements above the background, without making use of much atmospheric transport information (Hakkarainen et al, 2016;Kort et al, 2012;Schneising et al, 2013;Silva and Arellano, 2017;Silva et al, 2013). However, due to this simplification, the linkage between derived urban CO 2 emission signals and upstream sources is tenuous, as downwind XCO 2 can be enhanced not only by near-field upwind urban activities (e.g., traffic, houses, and power plants/industries), but also by regional-scale advection of upwind sources/sinks.…”
Section: Introductionmentioning
confidence: 99%